Focal signs in infantile spasms. (March 2022) - Haneder, Carmen; Stark, Birgit; Peherstorfer, Anna; Gröppel, Gudrun
Abstract: Background: Infantile spasms belong to the group of epileptic encephalopathies that typically occur in early infancy and are often associated with severe developmental delay. Little is known about whether focal features are part of the syndrome and thus occur independently of etiology, or whether focal features always indicate a cerebral lesion. Methods: In our study we included all patients with infantile spasms documented by prolonged video-electroencephalogram (EEG) monitoring between 7/2003 and 11/2020 and analysed symptoms such as tonic posturing, clonic movements, deviation of the eyes and unilateral deviation of the mouth. These symptoms were classified as lateralizing or non-lateralizing and the correlation to the presence of a lesion was investigated. Results: Eighteen patients (9 w/9 m) were included in the study. Lateralizing tonic posturing was found in 66.6% of the patients. Deviation of the eyes to one side and unilateral deviation of the mouth were detected in 61.1% and 11.1% of patients, respectively. Taking into account all symptoms (tonic posturing, clonic movements, deviation of the eyes, unilateral deviation of the mouth), focal signs were observed in a total of 94.4%, with only half of the total patient population having a cerebral lesion. Conclusion: In our study, lateralizing symptoms in infantile spasms occurred independently of the presence of a lesion. In contrast, focal symptoms in older children or adults usually correlate with the presence and localization of a lesion. A possible hypothesis could be that the brain is still maturing in infancy.